1996
DOI: 10.1111/j.1751-1097.1996.tb03090.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Responses of Amphibians to Solar and Artificial UVB Sources: A Comparative Study

Abstract: Many amphibian species, in widely scattered locations, currently show population declines and/or reductions in range, but other amphibian species show no such declines. There is no known single cause for these declines. Differential sensitivity to UVB radiation among species might be one contributing factor. We have focused on amphibian eggs, potentially the most UVB-sensitive stage, and compared their resistance to UVB components of sunlight with their levels of photolyase, typically the most important enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 32 publications
(30 reference statements)
4
83
1
1
Order By: Relevance
“…Amphibian populations are in serious decline in many areas of the world [151], and scientists are seeking explanations for this phenomenon [152,153]. Worrest and Kimeldorf [154] noted several adverse effects of increased exposure to UV-B radiation on the systemic development of boreal toad (Bufo boreas boreas) tadpoles in the laboratory.…”
Section: Secondary Consumersmentioning
confidence: 99%
“…Amphibian populations are in serious decline in many areas of the world [151], and scientists are seeking explanations for this phenomenon [152,153]. Worrest and Kimeldorf [154] noted several adverse effects of increased exposure to UV-B radiation on the systemic development of boreal toad (Bufo boreas boreas) tadpoles in the laboratory.…”
Section: Secondary Consumersmentioning
confidence: 99%
“…One study that has done so demonstrated that UV-B-induced spinal curvature in tadpoles can ultimately lead to death by causing them to swim in circles and thus preventing them from foraging [11]. Similarly, other UV-B-induced malformations and abnormalities such as oedema or bloating [21,22], eye abnormalities [23,24] and hindlimb malformations [12] may also negatively affect foraging ability, predator evasion and reproductive success, but, critically, these possibilities have not been tested directly. Other studies have measured correlates of fitness such as locomotor performance, predator-induced morphological defences, anti-predator behaviour, and age and size at metamorphosis [25 -31], and have demonstrated that these are negatively impacted by exposure to UV-B [10,14,16,32], but, again, none of these studies measured the fitness variables that these parameters are meant to be correlated to (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the 1-nM OP exposure is approximately 2,800 times less than the calculated LC 50 for R. pipiens tadpoles. The observed effects of UV-B on gene expression are in addition to the well-characterized effects of this stressor on several aspects of amphibian development and survival (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Severe deformities including lordosis (curvature of the spine), bloating/distension, and abnormal development of the presumptive cornea were common pathologies associated with UV-B exposure (13,14). Ankley et al (15) reported symmetrical hind-limb ectromelia and ectrodactyly after R. pipiens tadpoles were exposed to low levels (44 µW/cm 2 ) of UV-B.…”
mentioning
confidence: 99%
See 1 more Smart Citation